The Influence of Village Fund Allocation and Communication on Community Welfare Through Development in Bawosalo'o Siwalawa Village, Lolowa'u District, South Nias Regency - Halawa, Suprianus; Halawa, Yehezkiel; Dalimunte, Nurul (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The objective of the research was to examine the Effect of Village Fund Allocation on Community Welfare. This research is using primary data with method of collecting data used was distributing questionnaires directly. Population in this research is the People in lolowa’u, Alir Bawosalo’o Siwalawa. Statistical analysis used in this research is Multiple Linear Analysis using the help of SPSS (Statistical Package For The Social Science).The research method used is quantitative research. The results showed that the Allocation of Village Funds Has a Positive and Significant Effect on The Welfare of the Community.